THE UTILIZATION OF CORNCOB CHARCOAL BRIQUETTES AS A FUEL SOURCE FOR HOUSEHOLD NEEDS - Tambing, Enos; Agustinus, Agustinus; Joni, Joni; Allo, Elisabeth Payung (LPPM Univ. Ibn Khaldun Bogor, 2025)
This initiative aimed to address the issue of post-harvest corncob waste and the community's dependence on fossil fuels in Bibiosi Village, Keerom Regency. Through training on the production and utilization of charcoal briquettes from corncob waste, this community service program focused on improving energy efficiency, reducing household expenses, and fostering biomass-based entrepreneurship. The methods employed included socialization, technical training on briquette production (drying, carbonization, molding), and application testing in cooking. The test results indicated that the charcoal briquettes were capable of boiling 1 liter of water in 15 minutes and 10 seconds at an average temperature of 442°C, grilling 20 chicken skewers in 18 minutes and 12 seconds (438°C), and roasting 8 fish in 24 minutes and 35 seconds (429°C). These briquettes produced minimal smoke, left no soot, and were more economical than conventional fuels. In conclusion, corncob charcoal briquettes have the potential to serve as a sustainable solution for household energy and agricultural waste management.